Enhancing speech perception in challenging acoustic scenarios for cochlear implant users through automatic signal processing - Buechner, Andreas; Bardt, Michael; Kliesch, Sven; Lenarz, Thomas; Brendel, Martina (Frontiers in Audiology and Otology, 2024)
Objectives This clinical study investigated the impact of the Naída M hearing system, a novel cochlear implant sound processor and corresponding hearing aid, featuring automatic scene classification systems which combine directional microphones and noise reduction algorithms, on speech perception in various acoustic scenarios. Methods Speech perception was assessed in 20 cochlear implant (CI) recipients, comprising both bilaterally implanted and bimodal listeners. Participants underwent the adaptive matrix sentence test in both quiet and noisy environments. The automatic scene classifier (ASC, AutoSense OS 3.0) involving different microphone settings was evaluated against the omni-directional microphone on the Naída M hearing system. The predecessor hearing system Naída Q served as reference. Furthermore, the automatic focus steering feature (FSF, Speech in 360°) of the Naída M hearing system was compared to the manual FSF of the Naída Q hearing system in a multi-loudspeaker setup. Results While both sound processor models yielded comparable outcomes with the omni-directional microphone, the automatic programs demonstrated an enhancement in speech perception: up to 5dB or 40% in noise for the latest sound processor relative to its predecessor. Subjective feedback further underscored the positive experience with the newer generation system in everyday listening scenarios. Conclusion The latest Naída M hearing system features advanced classification systems combined with superior processing capabilities, significantly enhancing speech perception in noisy environments compared to its predecessor, the Naída Q hearing system.